Determinants of Centralized Public Procurement Effectiveness: Evidence from Selected Ethiopian Higher Public Education Institutions - Kedir Yusuf Abrahim; Ganfure Tarekegn (Journal of International Trade, Logistics and Law, 2020)
This study focuses on factors affecting centralized procurement system effectiveness in higher Ethiopian public educational Institutions. To achieve this objective the researchers employed the explanatory research design with a primary data sources from 82 employees through questionnaires and interview in purposively selected of public educational Institutions and Public property procurement team leaders of PPPDSA at federal level. The Pearson correlation analysis outcome showed that all explanatory variables were positively influencing the effectiveness of centralized procurement system but at different degree of correlation. The multiple linear regression analysis result of the study also revealed that public policy, control activities and staffs’ educational competency of sampled public education institutions strongly and positively affected centralized procurement system effectiveness at 4.2 percent, 0.01 percent and 0.01 percent respectively. Similarly, monitoring and contract management affected the centralized procurement system effectiveness at 0.00.01 and 5.2 percent respectively. Therefore, to avoid the return of defect goods, malpractices, high compliance and untimely response of procurement orders, the PPPDS and sampled Ethiopian higher public educational Institutions should design very clear procurement planning criteria that fits the national procurement guideline, strong internal control system with good evaluation system. Moreover, it also advisable if the sampled Ethiopian higher public educational institutions train their staffs that partake in procurement processes and apply a computerized procurement system to support their procurement policies and further improve their overall centralized procurement system effectiveness.